2017
DOI: 10.1007/s13353-017-0403-8
|View full text |Cite
|
Sign up to set email alerts
|

Abiotic stresses influence the transcript abundance of PIP and TIP aquaporins in Festuca species

Abstract: Festuca arundinacea and F. pratensis are the models in forage grasses to recognize the molecular basis of drought, salt and frost tolerance, respectively. Transcription profiles of plasma membrane intrinsic proteins (PIPs) and tonoplast intrinsic proteins (TIPs) aquaporin genes were obtained for leaves of Festuca species treated with different abiotic stimuli. F. arundinacea plants were exposed to drought and salt stress, whereas F. pratensis plants were cold-hardened. Changes in genes expression measured with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 70 publications
2
25
0
Order By: Relevance
“…In Festuca pratensis, TIP cold acclimation was associated with a lower transcript level of the FpTIP1;1 gene in the leaves in both the high and low frost-tolerant genotypes. The authors concluded that the down-regulation of these isoforms during the exposure to cold may be one of the cold-acclimation components that prevents frost-induced cellular dehydration [90]. A similar pattern of expression was observed in roots in rice (Oryza sativa L.) under cold treatment.…”
Section: Drought Salinity and Cold Stressmentioning
confidence: 72%
See 2 more Smart Citations
“…In Festuca pratensis, TIP cold acclimation was associated with a lower transcript level of the FpTIP1;1 gene in the leaves in both the high and low frost-tolerant genotypes. The authors concluded that the down-regulation of these isoforms during the exposure to cold may be one of the cold-acclimation components that prevents frost-induced cellular dehydration [90]. A similar pattern of expression was observed in roots in rice (Oryza sativa L.) under cold treatment.…”
Section: Drought Salinity and Cold Stressmentioning
confidence: 72%
“…In turn, in Festuca arundinacea, the plants were exposed to salt stress by irrigating them with 250 mM NaCl solution over 21 days, which resulted in an increase in the abundance of the FaTIP1;1 transcript in two contrasting salt tolerance genotypes compared to the control conditions. This increase was noticed earlier on day six of the NaCl treatment in the high-salt tolerant (HST) genotypes and later on day 11 in the low-salt tolerant (LST) genotype [90].…”
Section: Drought Salinity and Cold Stressmentioning
confidence: 95%
See 1 more Smart Citation
“…In F. arundinacea, drought resistance is mostly manifested by a drought avoidance strategy which relies on the development of deep root system, leaf rolling and a rapid stomatal closure (5,11). However, our earlier experiments revealed that F. arundinacea could also develop a drought tolerance strategy mainly associated with the adjustment of leaf metabolism to water deficit in plant tissues (5,6). On the other hand, F. glaucescens was described earlier as a species characterized mainly by a metabolism slowdown and a reduction of growth associated with a quiescence under drought conditions, followed by a further recovery after stress cessation, which enables it to survive and to resume the growth following irrigation (12,13).…”
Section: Introductionmentioning
confidence: 96%
“…Our previous studies revealed that Festuca species could be successfully used as models to precisely dissect mechanisms of resistance to a wide range of abiotic stresses in a group of forage grasses (e.g. 3,4,5,6,7,8,9).…”
Section: Introductionmentioning
confidence: 99%